THE EFFECT OF USING ANIMATED VIDEO ON THE LISTENING COMPREHENSION OF GRADE IX STUDENTS AT UPTD SMP NEGERI 5 PEMATANG SIANTAR - Novita Forena Simanungkalit; Bloner Sinurat; Mungkap Mangapul Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The goal of this research is to ascertain the effect of using animated video on the listening comprehension of Grade IX students at UPTD SMP Negeri 5 Pematangsiantar in the 2022/2023. Quantitative research approach is used in this research design. This type of research is a Quasi Experiment with a two-group static design. The dependent variable is the students' listening comprehension narrative text in monologue form as a learning material and the independent variable is the use of Animated video. The research subjects were grade IX at UPTD SMP Negeri 5 Pematangsiantar in the 2022/2023 academic year. The object of this research is the effect of animated video on the listening comprehension. The instruments used in this research were tests, pre-test and post-test. After the data has been collected, data analysis is carried out by comparing the results of the mean. The results showed that the mean of experimental group in pre-test is 60.3 and in post-test is 84.5 while the mean of control group in pre-test 53.2 and in post-test is 73.5. It showed that the score of the experimental group was higher than control group. The result of the t-test formula analysis showed that the value of t-test was higher than that of t-table, The t-test score (2.7)> t-table demonstrated this (1.671). As a consequence, the Null Hypothesis (HO) was disproved and the Alternate Hypothesis (Ha) was accepted. It is concluded that using animated video as media learning significantly affects listening comprehension of grade IX students at UPTD SMP Negeri 5 Pematangsiantar as a media learning than using recording audio.